Benchmarking quantum tomography completeness and fidelity with machine learning. (14th October 2021) - Teo, Yong Siah; Shin, Seongwook; Jeong, Hyunseok; Kim, Yosep; Kim, Yoon-Ho; Struchalin, Gleb I; Kovlakov, Egor V; Straupe, Stanislav S; Kulik, Sergei P; Leuchs, Gerd; Sánchez-Soto, Luis L
Abstract: We train convolutional neural networks to predict whether or not a set of measurements is informationally complete to uniquely reconstruct any given quantum state with no prior information. In addition, we perform fidelity benchmarking based on this measurement set without explicitly carrying out state tomography. The networks are trained to recognize the fidelity and a reliable measure for informational completeness. By gradually accumulating measurements and data, these trained convolutional networks can efficiently establish a compressive quantum-state characterization scheme by accelerating runtime computation and greatly reducing systematic drifts in experiments. We confirm the potential of this machine-learning approach by presenting experimental results for both spatial-mode and multiphoton systems of large dimensions. These predictions are further shown to improve when the networks are trained with additional bootstrapped training sets from real experimental data. Using a realistic beam-profile displacement error model for Hermite–Gaussian sources, we further demonstrate numerically that the orders-of-magnitude reduction in certification time with trained networks greatly increases the computation yield of a large-scale quantum processor using these sources, before state fidelity deteriorates significantly.